Alkane from hydrodeoxygenation (HDO) combined with in-situ multistage condensation of biomass continuous pyrolysis bio-oil via mixed supports catalyst Ni/HZSM-5-γ-Al2O3. (April 2020) - Li, Zhiyu; Xu, Xiwei; Jiang, Enchen; Han, Ping; Sun, Yan; Zhou, Ling; Zhong, Peidong; Fan, Xudong
Abstract: Faced with fossil fuel depletion and increasing environmental concerns, the conversion of renewable biomass into fuels or chemicals is promising but extremely challenging due to the inertness and complexity of biomass. Therefore, in situ multistage condensation combined with the HDO of pyrolysis bio-oil was chosen to reduce the complexity and improve the quality of bio-oil. In addition, the activity and stability of the catalyst was enhanced. The bio-oil obtained via continuous pyrolysis was divided into four-stage depending on their boiling point via in situ multistage condensation. After HDO, the relative content of long-chain alkanes was over 80% for each stage bio-oil via mixed supported Ni/HZSM-5-γ-Al2 O3 catalyst. Especially, the main components in the 3rd oil (aqueous phase) were n -heneicosane (31.60%), icosane (5.13%) and n -heptadecane (4.36%) based on the highest HDO ratio. Moreover, the reaction mechanism was discussed via the HDO of model bio-oil. The main reaction pathway consisted of hydrogenation and dehydration reactions (HYD pathway), and a side reaction was the direct deoxygenation route (DDO pathway). This work provides a general and efficient pathway for directly converting biomass into valuable long chain alkanes. Graphical abstract: Image 1 Highlights: HDO upgrading of multistage condensation pyrolysis bio-oil was investigated. Mixed supports Ni/HZSM-5-γ-Al2 O3 showed the outstanding performance for upgrading. The relative content of long-chain alkanes was over 80% for upgraded bio-oils. More than 70.1% of HDO ratio of bio-oil after HDO.